Effect of cysteine mutagenesis on human IgE reactivity of recombinant forms of the major rye grass pollen allergen Lol p 1 - Nicole de Weerd; Prem L. Bhalla; Mohan B. Singh (Allergology International, 2003)
Background: Hypersensitivity to the group 1 grass pollen allergens is a significant causative factor in the onset of symptoms for hay fever sufferers. To better understand the IgE reactivity of the group 1 allergen from rye grass pollen, we sought to disrupt potential conformational IgE epitopes on recombinant (r) Lol p 1 by the specific replacement of the seven cysteine residues in the protein sequence. Methods: Site-directed mutagenesis on the Lol p 1 coding sequence was used to replace all seven cysteine residues with serine residues. rLol p 1 and the seven cysteine variants generated by this method were tested for comparative human IgE reactivity via western blot immunoscreening and densitometry. Results: Alteration of the cysteine residues at amino acid positions 72, 77, 83 and 139 of rLol p 1 was found to reduce the human IgE binding potential of the molecule. However, the most consistent reduction in human IgE reactivity was demonstrated by replacement of C77; human IgE antibodies showed an average 62.7% reduction in reactivity to this molecule. Conclusions: The present investigation has shown that at least one of the cysteine residues within the Lol p 1 protein contributes to the IgE binding properties of this allergen.